Math, asked by Itzheartcracer, 2 months ago

Question!
Evaluate the following
\sf \lim_{h\to 0}\dfrac{(a+h)^2 \;\sin(a+h)-a^2 \sin a}{h}

Answers

Answered by mathdude500
12

\large\underline{\sf{Solution-}}

Given expression is

\rm :\longmapsto\:\displaystyle\lim _{h \to 0}\dfrac{(a+h)^2 \;\sin(a+h)-a^2 \sin a}{h}

If we substitute directly h = 0, we get

\rm \:  =  \:\dfrac{(a+0)^2 \;\sin(a+0)-a^2 \sin a}{0}

\rm \:  =  \:\dfrac{a^2 \;sina-a^2 \sin a}{0}

\rm \:  =  \:\dfrac{0}{0}

which is indeterminant form.

So,

\rm :\longmapsto\:\displaystyle\lim _{h \to 0}\dfrac{(a+h)^2 \;\sin(a+h)-a^2 \sin a}{h}

can be rewritten as

\rm =\displaystyle\lim _{h \to 0}\dfrac{( {a}^{2}+{h}^{2}+2ah)\sin(a+h)-a^2 \sin a}{h}

\rm =\displaystyle\lim _{h \to 0}\dfrac{{a}^{2}\sin(a+h) +  {h}^{2}sin(a + h) + 2ahsin(a + h) -a^2 \sin a}{h}

can be re-arranged as

\rm =\displaystyle\lim _{h \to 0}\dfrac{{a}^{2}(\sin(a+h) - sina) +  {h}^{2}sin(a + h) + 2ahsin(a + h)}{h}

\rm ={a}^{2}\displaystyle\lim _{h \to 0} \frac{sin(a + h) - sina}{h} + \displaystyle\lim _{h \to 0} \frac{ {h}^{2}sin(a + h) }{h}  +  \displaystyle\lim _{h \to 0} \frac{2asin(a + h)}{h}

We know,

\boxed{ \tt{ \: sinx - siny = 2cos\bigg[\dfrac{x + y}{2} \bigg]sin\bigg[\dfrac{x - y}{2} \bigg]}}

So, using this identity, we get

\rm  = {a}^{2}\displaystyle\lim _{h \to 0} \frac{2cos\bigg[\dfrac{a + h + a}{2} \bigg]sin\bigg[\dfrac{a + h - a}{2} \bigg]}{h} + \displaystyle\lim _{h \to 0}hsin(a + h) + 2asina

\rm  = {a}^{2}\displaystyle\lim _{h \to 0} \frac{2cos\bigg[\dfrac{2a + h}{2} \bigg]sin\bigg[\dfrac{h}{2} \bigg]}{h} + 0 + 2asina

\rm \:  =  \:2 {a}^{2}\displaystyle\lim _{h \to 0}cos\bigg[\dfrac{2a + h}{2} \bigg] \times \displaystyle\lim _{h \to 0} \frac{sin\bigg[\dfrac{h}{2} \bigg]}{ \dfrac{h}{2}  \times 2} + 2asina

We know

\rm :\longmapsto\:\boxed{ \tt{ \: \displaystyle\lim _{x \to 0} \:  \frac{sinx}{x} \:  =  \: 1 \: }}

So, using this, we get

\rm \:  =  \: 2{a}^{2}cos\bigg[\dfrac{2a + 0}{2} \bigg] \times  \dfrac{1}{2}  + 2asina

\rm \:  =  \: {a}^{2} \: cosa + 2a \: sina

Hence,

\boxed{ \tt{ \: \displaystyle\lim _{h \to 0}\dfrac{(a+h)^2 \;\sin(a+h)-a^2 \sin a}{h} =  {a}^{2}cosa + 2asina}}

Additional Information :-

\rm :\longmapsto\:\boxed{ \tt{ \: \displaystyle\lim _{x \to 0} \:  \frac{tanx}{x} \:  =  \: 1 \: }}

\rm :\longmapsto\:\boxed{ \tt{ \: \displaystyle\lim _{x \to 0} \:  \frac{log(1 + x)}{x} \:  =  \: 1 \: }}

\rm :\longmapsto\:\boxed{ \tt{ \: \displaystyle\lim _{x \to 0} \:  \frac{ {e}^{x}  - 1}{x} \:  =  \: 1 \: }}

\rm :\longmapsto\:\boxed{ \tt{ \: \displaystyle\lim _{x \to 0} \:  \frac{ {a}^{x}  - 1}{x} \:  =  \: loga \: }}

\boxed{ \tt{ \: sinx  +  siny = 2sin\bigg[\dfrac{x + y}{2} \bigg]cos\bigg[\dfrac{x - y}{2} \bigg]}}

\boxed{ \tt{ \: cosx  +  cosy = 2cos\bigg[\dfrac{x + y}{2} \bigg]cos\bigg[\dfrac{x - y}{2} \bigg]}}

\boxed{ \tt{ \: cosx - cosy = -  \:  2sin\bigg[\dfrac{x + y}{2} \bigg]sin\bigg[\dfrac{x - y}{2} \bigg]}}

Similar questions